UTILIZATION OF AGILE METHODS TO DEVELOP EMPLOYEE INTERPERSONAL SKILLS: A SYSTEMATIC LITERATURE REVIEW - Fitroh, Fitroh; Hudaya, Fahmi; Hanif, Muhamad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: Interpersonal skills in employees are an important part of technology companies in achieving their goals through the development of skills in their employees. The application of agile methods for application development has been widely carried out by technology companies. The agile method has the main principle of communication between employees, requiring skills to face these principles. The method used in this study is the systematic literature review (SLR) method to know how the use of agile methods can develop interpersonal skills in karyawan. In the initial search conducted using the Publish or Perish application, 740 journals were found in the range of 2015 to 2022. Next, journal filtering and cluster search continued using Microsoft Excel, Zotero, Mendeley, and VOS Viewer applications, resulting in 53 journals selected based on Q1. In the final stage of screening, researchers re-screened 9 journals that were used as a reference regarding the use of agile methods to develop employee interpersonal skills. The results showed that the agile development method can affect the development of employee interpersonal skills. 11 skills develop because of the use of this agile development method including team working, emotional intelligence, negotiation and persuasion, problem-solving, communication skills, conflict resolution, decision making, time management, organizational skills, listening, and relationship building. Of the 11 skills, the most mentioned is team working. Keywords: agile development methods; interpersonal skills; literature review Abstrak: Interpersonal skill pada karyawan menjadi bagian penting bagi perusahaan teknologi dalam mencapai tujuannya melalui berbagai pengembangan keterampilan. Penerapan metode agile untuk pengembangan aplikasi sudah banyak dilakukan oleh perusahaan-perusahaan teknologi. Metode agile memiliki prinsip utama berupa komunikasi antar karyawan sehingga membutuhkan keterampilan untuk menghadapi prinsip-prinsip tersebut. Metode yang digunakan pada penelitian ini yaitu metode systematic literature review (SLR) dengan tujuan untuk mengetahui bagaimana pemanfaatan metode agile dapat mengembangkan interpersonal skill pada karyawan. Pada pencarian awal yang dilakukan menggunakan aplikasi Publish or Perish, ditemukan 740 jurnal pada rentang tahun 2015 sampai 2022. Selanjutnya, penyaringan jurnal menggunakan aplikasi Microsoft Excel dan Mendeley Desktop yang menghasilkan 53 jurnal yang dipilih berdasarkan penilaian kualitas. Pada tahap akhir penyaringan, peneliti menyaring kembali menjadi 9 jurnal yang digunakan sebagai acuan mengenai pemanfaatan metode agile untuk mengembangkan interpersonal skills karyawan. Hasil penelitian menunjukan bahwa metode agile development dapat mempengaruhi pengembangan interpersonal skill karyawan, faktanya terdapat 11 skill yang berkembang karena pemanfaatan metode agile development ini diantaranya adalah team working, emotional intelligence, negotiation and persuasion, problem solving, communication skills, conflict resolution, decision making, time management, organizational skill, listening, dan relationship building. Dari 11 skill tersebut yang paling banyak disebut yaitu team working. Kata kunci: interpersonal skills; metode agile development; literature review;